Analysis of micro-powder injection technology in metal injection molding process - Chen, Kah Pin (2014)
Metal Injection Molding (MIM) process has advantages of low cost, high performance and shape complexity. Thus, there is a growing demand for products manufactured by this process in commercial, domestic and military applications. This project aims to improve the quality of AMT products through comprehensive studies in both the mixing and injection processes. The critical loading for various materials was studied. In order to achieve efficient homogeneous mixing, the simultaneous study of various mixing process parameters affecting the homogeneity of the feedstock was conducted. The study showed that all four mixing parameters namely mixing time, mixing temperature, rotor blade speed and powder loading rate are significant to the homogeneity of feedstock. With the homogenous feedstock, identification of the significant parameters for injection was investigated for better improvement in the quality of the products. It was found that melting temperature affects the contents in the molded parts due to low degradation temperature of the binder and this results in a higher number of defective parts. An attempt to model the injection molding process for MIM parts using mold-flow was explored in order to better understand the flow path of the copper feedstock.